Prediction of n-AlGaAs/GaAs Schottky diode properties for milliwatt range application - Parimon, Norfarariyanti (IDOSI Publications, 2010)
The Schottky diodes enjoined with coplanar waveguides are investigated for applications in on-chip rectenna device application without insertion of a matching circuit. The design, fabrication, DC characteristics and RF-to-DC conversion of the A1GaAs/GaAs HEMT Schottky diode is presented. The RF signals are Well converted by the fabricated Schottky diodes with cut-off frequency up to 20 GHZ estimated in direct inj ection experiments. Preliminary investigation on design, fabrication and DC and RF characteristics of the integrated device (planar dipole antenna Jr Schottky diode) on AlGaAs/GaAs structure is also presented. From the preliminary direct irradiation experiments using the integrated device, the Schottky diode is not turned on due to Weak reception of RF signal by dipole antenna. Further extensive considerations on the polarization of irradiation etc. need to be carried out in order to improve the signal reception. The outcomes of these results provide conduit for breakthrough designs for ultra-low power ori-chip recterma device technology to he integrated in nanosystems.